Cooperative spectrum sensing in a medium-traffic primary network using double-threshold scheme over imperfect reporting channels - Rabiee, Ramtin (2015)
The status of a primary user (PU) within sensing time is one of the important parameters, which is considered to be fixed in many studies of spectrum sensing in cognitive radio networks. In this paper, we consider a medium traffic of a primary network, in which the PU changes its state (either idle or active) at most once during the sensing period of the secondary user (SU). This situation degrades the detection performance of the secondary network. We first try to find a suitable distribution for observed energy levels by SUs, and then evaluate the detection performance of the both single- and double-threshold methods in terms of the total error probability using cooperative spectrum sensing over imperfect reporting channels. The results show that the double-threshold scheme outperforms the single one.